Transition‐Metal Oxides/Carbides@Carbon Nanotube Composites as Multifunctional Electrocatalysts for Challenging Oxidations and Reductions. Issue 47 (28th July 2019) - Xing, Xiaolin; Liu, Rongji; Cao, Kecheng; Kaiser, Ute; Streb, Carsten
Abstract: The rapid development of renewable‐energy technologies such as water splitting, rechargeable metal–air batteries, and fuel cells requires highly efficient electrocatalysts capable of the oxygen‐reduction reaction (ORR) and the oxygen‐evolution reaction (OER). Herein, we report a facile sonication‐driven synthesis to deposit the molecular manganese vanadium oxide precursor [Mn4 V4 O17 (OAc)3 ] 3− on multiwalled carbon nanotubes (MWCNTs). Thermal conversion of this composite at 900 °C gives nanostructured manganese vanadium oxides/carbides, which are stably linked to the MWCNTs. The resulting composites show excellent electrochemical reactivity for ORR and OER, and significant reactivity enhancements compared with the precursors and a Pt/C reference are reported. Notably, even under harsh acidic conditions, long‐term OER activity at low overpotential is reported. In addition, we report exceptional activity of the composites for the industrially important Cl2 evolution from an aqueous HCl electrolyte. The new composite material shows how molecular deposition routes leading to highly active and stable multifunctional electrocatalysts can be developed. The facile design could in principle be extended to multiple catalyst classes by tuning of the molecular metal oxide precursor employed. Abstract : All in one : A facile one‐pot synthetic route to convert the molecular manganese vanadium oxide precursor [Mn4 V4 O17 (OAc)3 ] 3− into nanoscale manganese–vanadium oxide/carbide particles is reported. Simultaneously, the particles are deposited on surface‐functionalized multiwalled carbon nanotubes. The composites show excellent electrochemical reactivity for oxygen evolution and reduction as well as the industrially important chlorine evolution reaction (see figure).